Hemophagocytic Lymphohistiocytosis Possibly Triggered by Craniotomy Surgery: A Rare Association with Uplifting Ending - Nandita, Lubna Ahmed; Taimor Newaz; Muquith, Tangia (Bangladesh Critical Care Journal, 2023)
Hemophagocytic lymphohistiocytosis (HLH) is an aggressive and life-threatening syndrome of excessive inflammation and tissue destruction due to abnormal immune activation. HLH can occur as a familial or sporadic disorder, as well as can be triggered by a variety of events that disrupt immune homeostasis. In HLH, natural killer cells and cytotoxic lymphocytes fail to eliminate activated macrophages resulting in excessive CD8+ T cell and activation of more macrophages with highly elevated levels of interferon-gamma and other cytokines, which drive the pathology of HLH. Here, we present a case of 15 years old boy with HLH, which possibly was triggered after surgical intervention for arachnoid cyst in the right parietal lobe. It was a daunting challenge for us to evaluate and diagnose the patient promptly since he was critically ill and developed pancytopenia, along with grossly altered liver function test and markedly raised ferritin in a short period of time. But it was even more crucial to start treatment in the form of chemotherapy in such a patient who had very severe neutropenia as well as thrombocytopenia. Bangladesh Crit Care J March 2023; 11 (1): 39-42